Initial Results From the GEM Challenge on the Spacecraft Surface Charging Environment. Issue 2 (21st February 2019) - Yu, Yiqun; Rastätter, Lutz; Jordanova, Vania K.; Zheng, Yihua; Engel, Miles; Fok, Mei‐Ching; Kuznetsova, Maria M.
Abstract: Spacecraft surface charging during geomagnetically disturbed times is one of the most important causes of satellite anomalies. Predicting the surface charging environment is one prevalent task of the geospace environment models. Therefore, the Geospace Environment Modeling (GEM) Focus Group "Inner Magnetosphere Cross‐energy/Population Interactions" initiated a community‐wide challenge study to assess the capability of several inner magnetosphere ring current models in determining surface charging environment for the Van Allen Probes orbits during the 17 March 2013 storm event. The integrated electron flux between 10 and 50 keV is used as the metrics. Various skill scores are applied to quantitatively measure the modeling performance against observations. Results indicate that no model consistently perform the best in all of the skill scores or for both satellites. We find that from these simulations the ring current model with observational flux boundary condition and Weimer electric potential driver generally reproduces the most realistic flux level around the spacecraft. A simple and weaker Volland‐Stern electric field is not capable of effectively transporting the same plasma at the boundary toward the Earth. On the other hand, if the ring current model solves the electric field self‐consistently and obtains similar strength and pattern in the equatorial plane as the Weimer model, the boundary condition plays another crucial role in determining the electron flux level in the inner region. When the boundary flux spectra based on magnetohydrodynamics (MHD) model/empirical model deviate from the shape or magnitude of the observed distribution function, the simulation produces poor skill scores along Van Allen Probes orbits. Key Points: Ring current models participated in GEM challenge to simulate surface charging environment along Van Allen Probes during 17 March 2013 Integrated electron flux over 10 keV is used as the major metric and evaluated against observations with various skill scores Evaluation indicates that no models excel at all skill scores; flux boundary conditions and electric field influence the model performance